2018
DOI: 10.1002/pssr.201800025
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Optical Properties of Sb2S3 Film Thermally Evaporated from Antimony Pentasulfide and Efficient Planar Solar Cells

Abstract: Antimony sulfide (Sb2S3) thin film is a promising light absorber for solar cell application due to its suitable bandgap, high absorption coefficient, and non‐toxic constituents. However, thermally evaporated Sb2S3 thin films experience sulfur loss during evaporation and post‐annealing, which do harm to the film quality and the performance of the devices. In this work, for the first time Sb2S3 thin films are prepared by thermally evaporating antimony pentasulfide (Sb2S5) precursor. The thermal and microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…For the device based on P-Sb 2 S 3 film, it delivers a short-circuit current density (J sc ) of 15.15 mA cm À2 , open-circuit voltage (V oc ) of 0.67 V and fill factor (FF) of 51.1%, corresponding to a PCE of 5.2%. This efficiency is higher than the reported device efficiency with thermal evaporation derived Sb 2 S 3 film in literature which is generally below 5% [14,22,23]. With regard to sulfur doping, the device generates a PCE of 5.8%.…”
Section: Resultscontrasting
confidence: 55%
“…For the device based on P-Sb 2 S 3 film, it delivers a short-circuit current density (J sc ) of 15.15 mA cm À2 , open-circuit voltage (V oc ) of 0.67 V and fill factor (FF) of 51.1%, corresponding to a PCE of 5.2%. This efficiency is higher than the reported device efficiency with thermal evaporation derived Sb 2 S 3 film in literature which is generally below 5% [14,22,23]. With regard to sulfur doping, the device generates a PCE of 5.8%.…”
Section: Resultscontrasting
confidence: 55%
“…4,D, Figure S9C,D) range from 100 nm to over 10 µm in size. These agglomerates, consisting of smaller grains separated by ridges, resemble the surface morphology of 300 nm thick polycrystalline Sb 2 S 3 films grown via thermal evaporation and annealed for 10 min at 300 °C in N 2 [35], and that of metal halide perovskites obtained by Volmer–Weber growth via hot casting [36]. The layers deposited at 220 °C from both Sb/S 1:3 and Sb/S 1:6 solutions, and thermally treated at 170 °C, consist of numerous grains and pinholes (3-220-170, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that by adapting a two-step sequence, whereby amorphous Sb 2 S 3 layers are first deposited by USP and then crystallized by thermal annealing, compact Sb 2 S 3 thin films with uniform thickness can be fabricated [46]. Similarly, a two-step procedure to grow compact Sb 2 S 3 thin films has become common practice for many deposition techniques [1820 27,29,31,35,47]. To summarize: in order to achieve progress in the various areas of PV applications, e.g., BIPV, and to increase the availability of PV beyond the state-of-the-art in compliance with ever stricter safety and health regulations, novel thin film solar cell designs are required, using abundant non-toxic materials and implementing cost-effective solar cell fabrication technologies.…”
Section: Introductionmentioning
confidence: 99%